GROWTH DETERMINATION OF TROPICAL LIMPET Cellana testudinaria (Linnaeus, 1758) LIVING ON THE ROCKY SHORE OF OHOIWAIT, SOUTHEAST MOLUCCAS, INDONESIA - Abraham S Khow (JOURNAL OF COASTAL DEVELOPMENT, 2007)
Monthly shell-length frequency distributions were used to analyse the size and age structure of the limpet population inhabiting the rocky shore of Ohoiwait, Southeast Moluccas. The lengths of the collected specimens ranged from 8.0 to 31.8 mm. The analysis of the successive frequency distributions suggested that the population consisted of 4 to 5 distinct age groups (cohorts) at any given time, and that two new cohorts recruited during the one-year investigation period. An analysis to determine growth pattern using FiSAT software showed that the longevity of C. testudinaria extended up to 2 years. The values of von Bertalanffy growth parameters (L¥, K and t0), estimated from size-frequency distributions, were 33.1 mm, 1.4 yr-1, and 0.09, respectively. The highest growth increments were 25% and 18% of the asymptotic length during the first 3 and 6 months, respectively. The effects of environmental variables on the growth rates showed important seasonal variations, with the highest increment of 2.6 mm/month during dry season. Here, growth parameter of C. testudinaria limpet shows the same value as other tropical limpets and depends on environmental variables.